Role of Vaspin in Human Eating Behaviour - Breitfeld, Jana; Tönjes, Anke; Gast, Marie-Therese; Schleinitz, Dorit; Blüher, Matthias; Stumvoll, Michael; Kovacs, Peter; Böttcher, Yvonne (PLOS ONE, 2013)
Objective The adipokine vaspin (visceral adipose tissue derived serine protease inhibitor, serpinA12) follows a meal-related diurnal variation in humans and intracerebroventricular vaspin administration leads to acutely reduced food intake in db/db mice. We therefore hypothesized that vaspin may play a role in human eating behaviour. Materials and Methods We measured serum vaspin concentrations in 548 subjects from a self-contained population of Sorbs (Germany) who underwent detailed metabolic testing including eating behaviour assessments using the three-factor eating questionnaire. In addition, genetic variation within vaspin was assessed by genotyping 28 single nucleotide polymorphisms (SNPs) in all study subjects. Results Serum vaspin concentrations correlated positively with restraint, disinhibition and hunger (all P<0.05), although the correlations did not withstand further adjustments for age, gender and BMI (all P>0.05). Independent of observed correlations, genetic variants in vaspin were associated with serum vaspin levels but showed no significant association with any of the eating behaviour phenotypes after accounting for multiple testing (P≥0.05 after adjusting for age, gender and BMI). Conclusion Our data suggest that serum vaspin concentrations might modulate human eating behaviour, which does not seem to be affected by common genetic variation in vaspin.